2016
DOI: 10.1016/j.reth.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

In vivo maturation of human embryonic stem cell-derived teratoma over time

Abstract: Transformation of human embryonic stem cells (hESC) is of interest to scientists who use them as a raw material for cell-processed therapeutic products. However, the WHO and ICH guidelines provide only study design advice and general principles for tumorigenicity tests. In this study, we performed in vivo tumorigenicity tests (teratoma formation) and genome-wide sequencing analysis of undifferentiated hESCs i.e. SEES-1, -2 and -3 cells. We followed up with teratoma formation histopathologically after subcutane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Interestingly, Akutsu et al . reported that teratomas derived from hESCs histologically matured in vivo over time [ 27 ]. Therefore, the formation of immature teratomas in vivo is regarded as a quality attribute of hPSCs, and immaturity of teratomas largely depends on the duration of hPSC transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Akutsu et al . reported that teratomas derived from hESCs histologically matured in vivo over time [ 27 ]. Therefore, the formation of immature teratomas in vivo is regarded as a quality attribute of hPSCs, and immaturity of teratomas largely depends on the duration of hPSC transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…For comparison, we used iPSCs of healthy and diseased donors. iPSCs such as PAE-iPSCs, UtE-iPSCs, AM-iPSCs, and 201B7 have been generated from placental, endometrial, amniotic, and fibroblastic cells [8,9,[31][32][33][34].…”
Section: Teratoma Formationmentioning
confidence: 99%
“…SEES" ESCs were routinely cultured onto a feeder layer of freshly plated gamma-irradiated mouse embryonic fibroblasts (MEFs), isolated from ICR embryos at 12.5 gestations and passages 2 times before irradiation (30 Gy), in the ESC culture media [15,16]. The ESC media…”
Section: Culture Of Escs Ipscs and Hepatocytesmentioning
confidence: 99%
“…In this study, we propagated hepatocytes or hepatocyte-like cells derived from human PSC, i.e. ESCs and iPSCs, and enriched zone I hepatocytes with ammonia [15,16]. Ammonia-selected cells proliferated in vitro at least up to 30 population doublings for more than 190 days.…”
Section: Introductionmentioning
confidence: 99%